DESIGN OF COASTAL PROTECTION STRUCTURE AT EAST GEBANG BEACH KABUPATEN CIREBON JAWA BARAT - Maulana Zuler, Giovani
Coastal areas and small islands have high potential and unique natural resources. This is influenced by the variety and quantity of natural potential with different characters in each region. Some of them are used for ponds, for example East Gebang Beach in Cirebon Regency, West Java. However, the movement of waves to the coast cause sediment transport which can cause accretion and abrasion, thus damaging various facilities in the area, especially community ponds. Besides the influence of currents and tides will also accelerate the erosion process that causes the coastline retreat. A coastline that is increasingly backward if left unchecked will certainly have an impact on the damage to community ponds. Therefore, to overcome this, it is necessary to plan the construction of coastal safeguards on the East Gebang Beach which is right at the points where the coastline changes have a major impact. Coastline setbacks caused by natural factors or human activities were analyzed using the Generalized Model for Simulating Shoreline Change (GENESIS) Coastal Engineering Design and Analysis System (CEDAS) module program. GENESIS will simulate coastline setbacks and implement appropriate coastal safeguards to overcome these setbacks. The beach safety building that is modeled is in the form of Groin, Breakwater, Revetment, and the combination / combination of these buildings. The results obtained that the appropriate beach safety structure is breakwater. Breakwater or building breakwaters selected amounted to 10 pieces with a length of 180 m each and placed at a distance of 160 meters from the coastline, and the distance between breakwater of 40 meters. The breakwater structure consists of an armor layer made of tetrapods, a filter layer and a core composed of natural stones of different sizes, and a toe protection layer.